Balkanları Konu Alan Romanlarda Osmanlı Algısı - Abdula, Sevba (4th International Balkan Studies Congress Proceedings, 2025)
In Turkish literature, historical novels are generally event-centered, focusing on war, campaigns, sieges, and heroism. When these narratives extend beyond Anatolia, the preferred geographical setting is often Central Asia. The subject of the Balkans in Turkish novels emerged with some delay. Since the 1960s, the Balkans have gradually started to appear in Turkish novels, and in recent years, there has been a notable acceptance and adoption of this region, surpassing the focus on Central Asia. The Balkans remained under Ottoman rule for five centuries, resulting in a significant Ottoman heritage in social, political, cultural, and other areas. The Turkish novel, which often addresses various so-cial issues, political developments, and cultural changes, has also explored this heritage from different perspectives. Key topics include the Ottoman establish-ment of order and peace in the Balkans, policies of tolerance, migrations, wars, sieges, and city reconstruction. In our study, we examine the approaches that shape the Ottoman perception in novels published between 1960-1980, which focus on the Balkans. Five novels that make this perception particularly visible and prominent were selected: Danube River Says Not to Flow, Balkan Pain, Bizim Diyar, Çiçek Büyür, and Azap Toprakları. The plots of these novels are set direct-ly in the Balkans, and their narrative characters are of Balkan origin, born and living in the region. This study explores how the Ottoman perception is depicted in these novels, which discourses are emphasized in constructing this percepti-on, and what approaches are used to critique the Ottoman Empire. Additionally, by analyzing and comparing the discourses in the novels, the study concretizes the common points and dominant views regarding the perception of the Otto-man Empire.